Invisible Oscillations in the Photodetachment Cross Section of $H^-$ near a Surface (Journal of Atomic and Molecular Sciences, 2021)
The photodetachment of $H^-$ near a surface is investigated. Alaser polarized parallel to the surface is used for the detachmentof the electron. Analytical expressions for the detached-electronflux and total photodetachment cross section are derived. Thedetached electron flux displays strong interference pattern on thescreen. Unlike the detached electron flux no visible oscillationsare found in the photodetachment cross section. Thephotodetachment cross section in low energy limits is double ofthe cross section of $H^-$ in free space.
Keywords: photodetachment; invisible oscillation; theoretical imaging method.